Antinociceptive effects of dexmedetomidine via spinal substance P and CGRP - Li Ruiqin; Qi Feng; Zhang Junlong; Ji Yong; Zhang Dengxin; Shen Zhiyun; Lei Weifu (Translational Neuroscience, 2015)
The aim of this study was to examine the role played by substance P and calcitonin gene-related peptide (CGRP) within the dorsal horn of the spinal cord in engagement of antinociception evoked by dexmedetomidine (DEX). Paw withdrawal threshold (PWT) to mechanical stimulation was determined after chronic intrathecal infusion of DEX and enzyme-linked immunosorbent assay (ELISA) was employed to examine the levels of spinal substance P and CGRP. Our results show that PWT was significantly increased by intrathecal administration of DEX in rats (P < 0.05 vs. vehicle control, n = 20 in each group). Also, intrathecal infusion of DEX significantly decreased the concentrations of substance P and CGRP as compared with vehicle control (P < 0.05 DEX vs. vehicle control, n = 20 in each group). Blocking α2-adrenoreceptors (α2-AR) blunted the decreases of substance P and CGRP levels and the enhancement of PWT evoked by DEX. Additionally, a linear relationship was observed between PWT and the levels of spinal substance P (r = 0.87; P < 0.005) and CGRP (r = 0.85; P < 0.005). Moreover, blocking individual substance P and CGRP receptors amplified PWT without altering substance P and CGRP levels. Thus, DEX plays a role in stimulating α2-AR receptors, which thereby decreases substance P and CGRP levels within the dorsal horn. This contributes to DEX-evoked antinociception.